A local structured training program with live pigs allows performing ESD along the gastrointestinal tract with results close to those of Japanese experts. Issue 12 (December 2016) - Jacques, Jérémie; Legros, Romain; Charissoux, Aurélie; Mesturoux, Laura; Couquet, Claude-Yves; Carrier, Paul; Tabouret, Tessa; Valgueblasse, Virginie; Debette-Gratien, Marilyne; Le-Sidaner, Anne; Loustaud-Ratti, Veronique; Sautereau, Denis
Abstract: Background and aims: The high specific skill needed by ESD limit its widespread use in Europe and animal training is recommended in Europe to improve the results of ESD that are far from Japanese at present. We create a local training program using live pigs as models, along with our human cases, to provide continuous exposure to the technique. Methods: Between February 2013 and December 2015, two young operators performed 55 pig gastric ESDs in parallel with 62 human cases for large superficial cancerous lesions. The number and training dates of pig cases were adapted to those of the human cases to achieve continuous exposure to ESD cases. Results: The en bloc, R0, and curative resection rates were 100%, 85.5% (53/62), and 77.5% (48/62), respectively with no recurrence observed during the one year follow up. There was no statistically significant difference in terms of the R0 or curative resection rates among ESDs performed during 2013–2015 (R0: 80% vs. 86.6% vs. 86.4%; Curative: 80% vs. 86.6% vs. 73%). Conclusion: A local structured training program using live pig models was used to train endoscopists for ESD in humans with high safety and efficiency, similar to results published by Japanese experts.